Cost-effectiveness of fractional exhaled nitric oxide (FeNO) measurement in predicting response to omalizumab in asthma - Brooks EA; Massanari M; Hanania NA; Weiner DJ (Dove Medical Press, 2019)
Elizabeth A Brooks,1 Marc Massanari,2 Nicola A Hanania,3 Daniel J Weiner11TTi Health Research & Economics, Health Research & Economics, Westminster, MD, USA; 2Circassia Pharmaceuticals, Global Medical Affairs, Morrisville, NC, USA; 3Section of Pulmonary and Critical Care Medicine, Baylor College of Medicine, Houston, TX, USAPurpose: To use a modeled analysis to examine the cost-effectiveness of utilizing fractional exhaled nitric oxide (FeNO) as a biomarker to aid in the identification of omalizumab responders in patients with moderate-to-severe allergic asthma. Omalizumab is a biological drug used to treat asthma in adults and children 12 years and older.Patients and methods: We conducted a decision analysis in which two alternative strategies for predicting omalizumab response were assessed: 1) testing response via a 12-week trial of omalizumab and 2) using FeNO measurement to screen patients for likely omalizumab response prior to initiating a 12-week trial of omalizumab. In the standard of care arm, trial omalizumab responders continue on to receive 12 months of continuous omalizumab therapy. In the FeNO measurement predictor arm, patients with FeNO measurements >19.5 ppb are started on a trial of omalizumab. Trial omalizumab responders in this arm are then also tracked for 12 months of continuous omalizumab therapy.Results: Per-patient costs during the trial and initial treatment periods total $10,943 for FeNO + omalizumab and $13,703 for omalizumab only. The expected cost per responder during the trial period is $4,326 for FeNO + omalizumab and $7,786 for omalizumab only.Conclusion: Use of FeNO measurement to identify omalizumab responders decreases the expected per-patient cost by nearly 50% during the trial period and continues to show cost savings through the initial treatment period of 12 months. Our analysis may serve as a model for policy and clinical practice regarding the use of FeNO to determine omalizumab response and has widespread implications for health care payers, who may choose to require FeNO measurement and prespecify a minimum FeNO value to determine patient eligibility for omalizumab trial.Keywords: FeNO, omalizumab, cost-effectiveness, asthma